2014
DOI: 10.1186/1471-2229-14-123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of boron-deficiency-responsive microRNAs in Citrus sinensis roots by Illumina sequencing

Abstract: BackgroundBoron (B)-deficiency is a widespread problem in many crops, including Citrus. MicroRNAs (miRNAs) play important roles in nutrient deficiencies. However, little is known on B-deficiency-responsive miRNAs in plants. In this study, we first identified miRNAs and their expression pattern in B-deficient Citrus sinensis roots by Illumina sequencing in order to identify miRNAs that might be involved in the tolerance of plants to B-deficiency.ResultsWe isolated 52 (40 known and 12 novel) up-regulated and 82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 94 publications
11
73
2
1
Order By: Relevance
“…In case of B deficiency, control and B-deficient root libraries were generated in Citrus sinensis for miRNAs identification and expression pattern analysis. In roots subjected to B starvation, 52 miRNAs were found with elevated expressions, while 82 were found downregulated, demonstrating marked flexibility of C.sinensis roots during B deficiency tolerance (Lu et al, 2014). This study also proposed several adaptation strategies of C. sinensis roots for B-deficiency tolerance based on the their results, mainly includes (1) perturbation of ROS signaling and scavenging due to elevated expression of miR474 and suppression of miR782 and miR843; (2) modifications in the lateral roots development in C. sinensis due to suppression of miR5023, which might upregulated its target gene expression ROOT HAIR DEFECTIVE3 (RHD3), which was previously reported as key factor involved in increase lateral roots formation in plants (Hajiboland et al, 2012); (3) upregulation of miR394 in roots possibly downregulated the accumulation of LEAF CURLING RESPONSIVE (LCR) mRNA, which lead to certain morphological changes specifically required for B-deficiency tolerance; (4) downregulation of miR830, miR5266 and miR3465 increased cell transport in vesicles and organelles by altering the expression of targets such as microtubule motor proteins (Kinesins) and autoinhibited Ca 2+ -ATPase 11; (5) increased the transcript of miR821 might suppressed its target gene (GDH1; NADP-dependent glutamate dehydrogenase), while decreased transcript of miR5023 in roots, conceivably altered several metabolic reactions due to targeting FK506-binding proteins (FKBP), cyclosporins (CyPs) and parvulin (Pvn) which are the three major classes of peptidyl prolyl cis-trans isomerases (PPIases) and are considered to assist chaperones by accelerating the slow rate-limiting isomerization steps.…”
Section: Mirnas Responsive To Mineral Elements (Cu Zn Fe Mn B)mentioning
confidence: 97%
“…In case of B deficiency, control and B-deficient root libraries were generated in Citrus sinensis for miRNAs identification and expression pattern analysis. In roots subjected to B starvation, 52 miRNAs were found with elevated expressions, while 82 were found downregulated, demonstrating marked flexibility of C.sinensis roots during B deficiency tolerance (Lu et al, 2014). This study also proposed several adaptation strategies of C. sinensis roots for B-deficiency tolerance based on the their results, mainly includes (1) perturbation of ROS signaling and scavenging due to elevated expression of miR474 and suppression of miR782 and miR843; (2) modifications in the lateral roots development in C. sinensis due to suppression of miR5023, which might upregulated its target gene expression ROOT HAIR DEFECTIVE3 (RHD3), which was previously reported as key factor involved in increase lateral roots formation in plants (Hajiboland et al, 2012); (3) upregulation of miR394 in roots possibly downregulated the accumulation of LEAF CURLING RESPONSIVE (LCR) mRNA, which lead to certain morphological changes specifically required for B-deficiency tolerance; (4) downregulation of miR830, miR5266 and miR3465 increased cell transport in vesicles and organelles by altering the expression of targets such as microtubule motor proteins (Kinesins) and autoinhibited Ca 2+ -ATPase 11; (5) increased the transcript of miR821 might suppressed its target gene (GDH1; NADP-dependent glutamate dehydrogenase), while decreased transcript of miR5023 in roots, conceivably altered several metabolic reactions due to targeting FK506-binding proteins (FKBP), cyclosporins (CyPs) and parvulin (Pvn) which are the three major classes of peptidyl prolyl cis-trans isomerases (PPIases) and are considered to assist chaperones by accelerating the slow rate-limiting isomerization steps.…”
Section: Mirnas Responsive To Mineral Elements (Cu Zn Fe Mn B)mentioning
confidence: 97%
“…Second, miR821 family has been demonstrated in response to stress and metabolic processes in potato (Xie et al, 2011). This miR821 family is known for boron-deficiency-responsive microRNAs in Citrus sinensis roots (Lu et al, 2014), low-N tolerance in rice genotypes (Nischal et al, 2012) and play a similar regulatory mechanism in Asiatic cotton (Wang et al, 2012b). Whereas, third miR1030 family may play important roles in growth and development of Solanaceae (Kim et al, 2011), down regulated under drought stress in rice (Zhou et al, 2010), adaptive response to abiotic stress in cotton (Boopathi and Pathmanaban, 2012) and cold-responsive miRNAs in peach (Barakat et al, 2012).…”
Section: Target Prediction Of Mirnas and Functional Analysismentioning
confidence: 99%
“…With the discovery of first miRNAs (lin-4 and let-7) in Caenorhabditis elegans (Olsen et al, 1999), in plants first miRNA was identified in Arabidopsis thaliana in 2002 (Park et al, 2002). Since then with the advent of modern computational tools and conserved nature of mature miRNAs, several miRNAs have been identified across the plant species such as potato (Xie et al, 2011;Yang et al, 2013;Zhang et al, 2013), Solanaceae plants (Kim et al, 2011), Arabidopsis (Liang et al, 2015), rice (Campo et al, 2013), wheat (Akdogan et al, 2015), Brassica juncea (Srivastava et al, 2013), chickpea (Kohli et al, 2014), citrus (Lu et al, 2014) and peach (Luo et al, 2013) to name a few. To date, a total of 24,521 distinct mature hairpin precursor miRNAs across 206 species have been annotated in the miRBase Release 20, an open online repository.…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRNAs) have been shown to represent an important class of transcription regulators in the eukaryotes (He et al, 2014;Asha et al, 2016;Niu et al, 2016). They inhibit transcription for the most part by interacting with their complementary mRNA, and in so doing target them for degradation (Tang et al, 2012;Lu et al, 2014). They are intimately involved in the adaptive response to both abiotic and biotic stress, and are regulated by complex gene networks (Kumar, 2014;Feng et al, 2015;Niu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%